The contribution of small shrubby patches to the functional diversity of wood-pastures - Oksuz, Duygu P. (2022)
Wood-pastures are grazed systems resulting from a long-term use of natural woodlands by humans. These social-ecological systems, covering vast areas of Europe and other temperate regions, have both high biodiversity and economic values, so many are classified as High Nature Value Farmlands. However, in some regions a loss of spatial heterogeneity threatens this natural value. We investigated the potential contribution of tiny shrubby patches to increase spatial heterogeneity and functional diversity in wood-pasture landscapes. Specifically, we compared functional composition (Community Weighted Means) and functional diversity (Functional Dispersion and Functional Evenness) of assemblages of plants, beetles and lichens in those patches (252–3000 m2) and in the wood-pasture matrix. We found that shrubby patches and matrix harbour species assemblages with very distinct functional compositions in all studied taxonomic groups. Evergreen, woody, broad-leafed and fleshy-fruited are better represented in the patches. In beetles, the main differences were a greater prevalence of small-sized and fungivore species in the patches. Shrubby patches also mostly harboured lichens with fruticose- and foliose-broad growth forms, a greater humidity preference, and lower eutrophication tolerance. Moreover, the two indexes used to quantify functional diversity (Functional Dispersion and Functional Evenness) show that, overall, diversity is greater in patches than in the matrix; in patches Functional Dispersion is statistically higher for plants, and Evenness is statistically higher for beetles and lichen. These differences are all consistent with the very distinct ecological conditions in the matrix and patches. The greater overall functional diversity of shrubby patches, and the major differences in functional composition between patches and matrix, observed for all taxa, indicate that these patches greatly enhance the functional diversity of species assemblages in wood-pasture landscapes. Consequently, preserving and promoting tiny shrubby patches is a potentially valuable low-cost management tool to increase biodiversity and improve ecosystem functioning in wood-pasture landscapes.